Phylogenetic relationships, morphological variation, and toxin patterns in the Alexandrium ostenfeldii (Dinophyceae) complex: implications for species boundaries and identities. Issue 1 (20th November 2013) - Kremp, Anke; Tahvanainen, Pia; Litaker, Wayne; Krock, Bernd; Suikkanen, Sanna; Leaw, Chui Pin; Tomas, Carmelo; De Clerck, O.
<x xml:space="preserve">Abstract</x> Alexandrium ostenfeldii (Paulsen) Balech and Tangen and A. peruvianum (Balech and B.R. Mendiola) Balech and Tangen are morphologically closely related dinoflagellates known to produce potent neurotoxins. Together with Gonyaulax dimorpha Biecheler, they constitute the A. ostenfeldii species complex. Due to the subtle differences in the morphological characters used to differentiate these species, unambiguous species identification has proven problematic. To better understand the species boundaries within the A. ostenfeldii complex we compared rDNA data, morphometric characters and toxin profiles of multiple cultured isolates from different geographic regions. Phylogenetic analysis of rDNA sequences from cultures characterized as A. ostenfeldii or A. peruvianum formed a monophyletic clade consisting of six distinct groups. Each group examined contained strains morphologically identified as either A. ostenfeldii or A. peruvianum. Though key morphological characters were generally found to be highly variable and not consistently distributed, selected plate features and toxin profiles differed significantly among phylogenetic clusters. Additional sequence analyses revealed a lack of compensatory base changes in ITS2 rRNA structure, low to intermediate ITS/5.8S uncorrected genetic distances, and evidence of reticulation. Together these data (criteria currently used for species delineation in dinoflagellates) imply that the A. ostenfeldii complex should be regarded a single genetically structured species until more material and alternative criteria for species delimitation are available. Consequently, we propose that A. peruvianum is a heterotypic synonym of A. ostenfeldii and this taxon name should be discontinued.